AGRIBUSINESS DEVELOPMENT BASED ON IMPROVED MATERIAL AND TECHNICAL RESOURCES AND COOPERATION - Kolotyrin, K.; Nursapina, K.; Ahmetzhanova, N.; Yessengaliyeva, S.; Kazambayeva, A.; Traissova, A. (TURISMO-ESTUDOS E PRATICAS, 2020)
The problem of effective agriculture functioning is associated with such factors as the development of small and medium agribusiness, cooperation, the development of the material and technical resources. In this connection, the article proposes the development of an organizational-economic mechanism of cooperation and the improvement of the agribusiness. Different variants of cooperation, increasing the efficiency of the agro-industrial complex, are described. Mutual benefits from agricultural cooperation for small and medium-sized businesses are substantiated.Проблема эффективного функционирования сельского хозяйства связана с такими факторами, как развитие малого и среднего агробизнеса, кооперация, развитие материально-технической базы. В связи с этим в статье предлагается разработка организационно-экономического механизма сотрудничества и совершенствование агробизнеса. Описаны различные варианты сотрудничества, повышающие эффективность агропромышленного комплекса. Обоснована взаимная выгода от сельскохозяйственной кооперации для малого и среднего бизнеса.
Keywords: импакт-фактор 2020; зарубежное издание; зарубежные авторы; научный журнал; дальнее зарубежье; экономика апк; томсон; периодическое издание; сельский бизнес